Family dominant hypothesis for the effect of family of origin on the mental health of offspring: evidence, mechanism, and implications - Dai, Zongpei; Luo, Yutong; Tan, Jieying; Hu, Li; Dai, Qin (Frontiers in Psychiatry, 2026)
Individuals suffering from mental illness often report an abnormal family of origin. Previous family theories have primarily focused solely on family risk factors or treated family members equally and have largely overlooked the critical role of family of origin in offspring development. In this study, we proposed a Family Dominant Hypothesis to emphasize the critical role of family of origin in the lifelong mental health of offspring. The core concept is that family and environmental variables, encompassing both risk and protective factors, contribute to different mental health outcomes in offspring, with the family of origin playing a directly dominant and indirectly mediating role in child development. This theoretical hypothesis highlights the dominant and mediating role of family of origin, considering both risk and protective factors--including biological genetics, family conditions, parental mental wellness, the relationship between parents, parenting style, and the parent-child relationship--in child development. Potential neurobiological mechanisms underlying the influence of the family of origin were also explored. Meanwhile, potential family interventions targeting the identified risk factors were proposed. The Family Dominant Theory is proposed to draw attention from society, particularly families and young parents, to emphasize the importance to family of origin environment. A comprehensive understanding of family of origin can help establish a healthier family environment and promote lifelong mental health of offspring.